ANALISIS TINGKAT DAYA SERAP ANGGARAN BELANJA DAERAH DI KOTA MALANG - Luluk Krisdiyanawati; M. Faisal Abdullah; Yunan Syaifullah (Jurnal Ilmu Ekonomi JIE, 2020)
The purpose of this research is to understand the level of absorptive capacity of regional expenditure budgets in Malang City and to understand the effect  of planning  variables, procurement of goods and services variables, and human sesource variables on the  absorption of regional expenditure budgets in Malang.  This type of research  is  quantitative  research. The population in this research were 20 regional work units in Malang in the form of Agency and Department. The sample of this research is the Regional  Financial and Asset Agency, Planning Research and Development Agency, Education and Culture Department, Health Department, and Environment Department in Malang City with  respondents occupying positions related to the budget, namely the authority  of  budgets users, officials making commitments, the technical executive officer of the  activity, the official signing the payment order, and the treasurer of the expenditure.The technical analysis used is multiple linear regression. The results of this research indicated that the human resources variable has a significant  positive effect on the absorption of regional budgets. While the planning variable and the procurement  of goods and services variable do not significantly positive influence the absorption capacity of the budget.